Flood Regulation Ecosystem Services Performance Based On Slope And Land Cover To Support Soil And Water Conservation In Ternate City - adriani; Muh. Faedly H. Tidore; Nurfadhilah Arif; Sabaruddin B (BANDAR: JOURNAL OF CIVIL ENGINEERING, 2026)
Ternate City is a multi-island municipality characterized by diverse topographic and ecological conditions, exposing it to significant risks of surface runoff, inundation, and flash floods, consequences of its steep volcanic terrain and rapid land cover change. Flood regulation ecosystem services play a critical role in soil and water conservation and sustainable spatial planning. This study assessed the performance of flood regulation ecosystem services based on slope gradient (landform) and land cover across Ternate City using secondary spatial data from the 2022 Environmental Carrying and Assimilation Capacity Document (D3TLH), computed via the Simple Additive Weighting (SAW) method with a 1" × 1" grid system (approximately 30 m²). Results indicate that flood regulation service performance is dominated by the medium class (41.99%), followed by the high-to-very high class (32.78%), and the low-to-very low class (25.23%). Batang Dua and Ternate Barat sub-districts exhibit the highest ecosystem service performance, with high-to-very high coverage accounting for 13.66% and 6.58% of total area, respectively. Dry Land Forest is the primary contributor to the very high class (27.82%), while plantation land cover dominates the medium class (40.90%). The Mid Volcanic Slope (11.37%) and Tectonic Hills (7.97%) landform units are the largest contributors to the very high class. These findings highlight the urgency of prioritizing soil and water conservation efforts in forested volcanic slopes and tectonic hill areas to sustain long-term flood mitigation capacity.